PENGUJIAN KARAKTERISTIK MOTOR KAPASITOR UNTUK BERBAGAI NILAI KAPASITANSI - Hamdani, Tajuddin (MEKTEK, 2005)
The aim of this research is to determine Â a value of capacities of capacitor on induction motor one phase with Â various capacities value. Data was collected with a testing procedure for several capacities value.The research comprised several capacitor value i.e, at respectively 2,533Î¼F, 7,18Î¼F and 8,24Î¼F. The result of this research indicated that big more and more motor burden hence current emiting a stream of big more and more, good power factor progressively and efesiensi increase. And larger ones capasitor value will cause power factor of leading, voltage will precede current